IMPROVING THE STRENGTH OF CEMENT PASTE BY MODIFYING THE CT MECHANICALLY ACTIVATED BY SMALL PARTICLES - and and (Municipal economy of cities. Series: «Economy science», 2013)
The possibility of increase strength cement by modification of the cement. The properties of the samples and performed the statistical analysis of the experimental results. The technological scheme production of concrete products using a modification cement activated by small particles.